2023
DOI: 10.32471/exp-oncology.2312-8852.vol-41-no-2.12973
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of HER-2/neu, с-MYC and CCNE1 gene copy number variations and protein expression in endometrial carcinomas

Abstract: Summary. Aim: To analyze copy number variations of HER-2/neu, c-MYC and CCNE1 oncogenes and their protein expression in endometrioid endometrial carcinomas in relation to the degree of tumor progression and presence of a family history of cancer in cancer patients. Materials and Methods: The study was conducted on endometrial cancer (EC) samples from 68 patients with I–II FIGO stages of disease. Copy number analysis of HER-2/neu, c-MYC and CCNE1 genes was performed by quantitative PCR. Protein expression was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…MYC amplification in EC has been reported in other studies [30,31]. In agreement with our results, MYC amplification along with HER-2/neu and cyclin E high protein expression have been associated with tumor progression, higher tumor grade and deep myometrial invasion in the literature [32]. Although MYC copy number and mRNA expression levels were not highly correlated, PVT1 was co-amplified with MYC (p<0.001) ( Fig 5) in 25% of the cases, and had a strong correlation with gene expression (r = 0.60).…”
Section: Plos Onesupporting
confidence: 93%
See 1 more Smart Citation
“…MYC amplification in EC has been reported in other studies [30,31]. In agreement with our results, MYC amplification along with HER-2/neu and cyclin E high protein expression have been associated with tumor progression, higher tumor grade and deep myometrial invasion in the literature [32]. Although MYC copy number and mRNA expression levels were not highly correlated, PVT1 was co-amplified with MYC (p<0.001) ( Fig 5) in 25% of the cases, and had a strong correlation with gene expression (r = 0.60).…”
Section: Plos Onesupporting
confidence: 93%
“…DNA hypermethylation of the upstream CEBPA promoter region is responsible for very low CEBPA expression in lung and endometrial cancers [36]. Decreased expression of CEBPA by posttranscriptional regulation was also shown in myeloid leukemia [32]. Therefore, CEBPA does not appear to be a likely candidate driver gene in ESC.…”
Section: Plos Onementioning
confidence: 99%
“…Endometrial carcinoma type I is frequently associated with alterations in phosphatase and tensing homologue deleted on chromosome 10 (PTEN), K-ras, β-catenin, phosphatidyl-inositol-3-kinase catalytic subunit (PIK3CA), MutL homolog (MLH)-1 and MLH-6, and alterations in DNA-mismatch repair genes and microsatellite instability (79,80). Endometrial carcinoma type II is frequently associated with alterations in p53, p16, human epidermal growth factor receptor type 2 (also known as proto-oncogene neu or receptor tyrosine-protein kinase, c-erbB-2), E-type Cyclin E1, c-MYC, fibroblast growth factor receptor 3, SOX17, STK15 and E-cadherin, including loss of heterozygosity (79)(80)(81)(82)(83)(84). Metabolic syndrome is accompanying by chronic proinflammatory status and is associated with the development of cardiovascular disease and diabetic morbidity and mortality (85,86).…”
Section: Discussionmentioning
confidence: 99%
“…The Myc family of transcription factors are one of the few master regulators of oncogenesis, as deregulation has been detected in over 70% of human cancers and associated with poor prognosis [ 71 ]. A study conducting immune histochemical stainings found a 78.3% positive rate of c-Myc in endometrial cancer tissues and an amplified c-Myc in 25% of the cases [ 72 , 73 ]. Additionally, high expression of c-Myc was more often observed in low differentiated endometrial cancers than moderately differentiated ones [ 73 ].…”
Section: Targeting Signaling Pathways In Endometrial Cancer Stem Cellsmentioning
confidence: 99%
“…A study conducting immune histochemical stainings found a 78.3% positive rate of c-Myc in endometrial cancer tissues and an amplified c-Myc in 25% of the cases [ 72 , 73 ]. Additionally, high expression of c-Myc was more often observed in low differentiated endometrial cancers than moderately differentiated ones [ 73 ]. Regarding endometrial carcinogenesis, upregulation of c-Myc in endometrial cancer cells was shown to induce EMT, drug resistance and invasion [ 74 , 75 ].…”
Section: Targeting Signaling Pathways In Endometrial Cancer Stem Cellsmentioning
confidence: 99%